Identification of Differentially Expressed Genes Reveal Conserved Mechanisms in the Rice-Magnaporthe oryzae Interaction - Liang, Dong; Qi, Zhongqiang; Du, Yan; Yu, Junjie; Yu, Mina; Zhang, Rongsheng; Cao, Huijuan; Pan, Xiayan; Qiao, Junqing; Song, Tianqiao; Liu, Youzhou; Chen, Zhiyi; et al. (Frontiers in Plant Science, 2022)
Magnaporthe oryzae causes rice blast disease and is responsible for major losses in rice production worldwide. Although numerous studies have focused on the interactions between Oryza sativa and M. oryzae, to date, the conserved mechanisms remain in part unclear. In this study, a comparative analysis of transcriptomes of O. sativa L. ssp. japonica cv. ‘Nipponbare’ interacting with three M. oryzae strains (248, 235, and 163) were performed to explore the conserved molecular mechanisms. Differentially expressed genes with similar expression patterns in the interactions between cultivar ‘Nipponbare’ and three M. oryzae strains were defined as Conserved Differentially Expressed Genes (CDEGs). These included 3,647 O. sativa CDEGs and 3,655 M. oryzae CDEGs. Four rice CDEGs (LOC_Os03g19270, LOC_Os07g36600, LOC_Os05g28740, and LOC_Os01g32780) encoding universal stress protein (USP) were induced within 24 h post-inoculation (hpi) by three M. oryzae strains. Meanwhile, overexpression of LOC_Os07g36600 resulted in enhanced rice resistance against M. oryzae. Furthermore, four rice genes coding light-harvesting chlorophyll a/b-binding (LHC) protein (LOC_Os02g52650, LOC_Os09g12540, LOC_Os11g13850, LOC_Os05g22730) were also identified as CDEGs and were induced at 48 hpi, which might contribute to blast resistance through reactive oxygen species (ROS) accumulation. MoCDIP4 is M. oryzae effector inducing rice cell death and were verified that include AA9 CAZy domain (namely GH61 domain). In this study, we found seven MoCDIP4-homologous genes coding proteins with signal peptides and AA9 CAZy domains, which were continuously up-regulated across all infection stages relative to uninoculated control. This study uncovered that genes are required for conserved mechanisms of rice-M. oryzae interaction, which includes rice genes encoding USP proteins and LHC proteins, as well as M. oryzae genes encoding AA9 proteins. This study will help us to understand how O. sativa responds to M. oryzae infections and the molecular mechanisms of M. oryzae pathogenicity.